Self-efficacy in Arabic Writing - Daud, Nadwah; Ghazuddin, Farhanah; Mustapha, Nik Hanan (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
The study aimed to determine the level of self-efficacy in writing skill among learners at International Islamic University Malaysia. The respondents were 200 learners from the Department of Arabic Language and Literature at this university. The instrument used was adapted from previous studies that measured writing self-efficacy. The results show that most learners had high level of self-efficacy in writing as well as its elements. However, in the writing process, the study discovers moderate level of self-efficacy among these learners. In terms of gender differences, there was no significant difference in self-efficacy between both male and female learners. Male learners reported higher level of self-efficacy in overall writing skill as well as its process and elements. When it comes to the level of study, the result indicates a significant difference between beginner and advanced learners. The advanced learners displayed greater level of self-efficacy than their counterparts in all parts of writing.